ANALISIS CERITA I LUTUNG TEKEN I KAKUA SEBAGAI MEDIA PEMBELAJARAN LITERASI ANAK DALAM PEMBELAJARAN BAHASA BALI - I Wayan Sujana; Ni Luh Ketut Ary Maharani; Ida Bagus Yoga Swadnyana; Komang Wida Yuniati; I Putu David Smarananda (STKIP Subang, 2026)
This study was conducted in response to the low literacy skills of elementary school students and the limited integration of local wisdom in Balinese language learning. The study aimed to analyze the literacy values contained in the folktale I Lutung teken I Kakua and examine its use as a learning medium in Balinese language learning at elementary schools. This study employed a qualitative descriptive approach using a literature review method. The primary data source was the folktale I Lutung teken I Kakua by I Nengah Tinggen, supported by various relevant studies on literacy and Balinese folktales. Data were collected through documentation techniques and analyzed descriptively through data reduction, data classification, and conclusion drawing. The results indicate that the folktale contains literacy values that support the development of listening, speaking, reading, writing, and critical thinking skills among students. In addition, the story presents moral and cultural values that contribute to character building and the preservation of local culture. Therefore, Balinese folktales serve as effective, contextual, and innovative literacy learning media in Balinese language learning at elementary schools.